DEVELOPMENT OF TEST INSTRUMENTS TO MEASURE MATHEMATICAL COMMUNICATION SKILLS OF MADRASAH IBTIDAIYAH STUDENTS - Farmah, Elisha; Novaliyosi; Hepsi Nindiasari; Nurul Anriani (Universitas Muhammadiyah Metro, 2026)
Mathematical communication skills are fundamental competencies that students must have, but there are no valid and reliable test instruments to measure the mathematical communication skills of Madrasah Ibtidaiyah students specifically. This research aims to develop valid, reliable, and practical mathematical communication ability test instruments for Madrasah Ibtidaiyah students. The research uses a Research and Development (R&D) approach with the Plomp model which includes the initial investigation, prototype phase, and assessment phase. The research subjects consisted of 39 students of class V MIN 1 Cilegon City who were selected using the purposive sampling technique. The instrument was developed based on the theoretical framework of NCTM with four mathematical communication indicators in KPK and FPB materials. The developed instrument met psychometric standards with very high construct validity (correlation coefficient r > 0.80 for all question items) and high reliability (α = 0.861). The distribution of difficulty level showed one question item in the medium category (65.40%) and three questions in the very difficult category (15.90%-17.80%). The differentiating power showed that one question item was categorized as sufficient (0.341) while the other three items needed improvement. The instrument was successfully developed with adequate psychometric quality and can be used as an evaluation tool for mathematical communication skills at Madrasah Ibtidaiyah. Further research is suggested to expand the research sample and develop instruments for other mathematical materials. Kemampuan komunikasi matematika merupakan kompetensi mendasar yang harus dimiliki siswa, namun tidak ada instrumen tes yang valid dan handal yang tersedia untuk secara khusus mengukur kemampuan komunikasi matematika siswa Madrasah Ibtidaiyah. Penelitian ini bertujuan untuk mengembangkan instrumen uji kemampuan komunikasi matematika yang valid, handal, dan praktis bagi siswa Madrasah Ibtidaiyah. Penelitian menggunakan pendekatan Research and Development (R&D) dengan model Plomp yang terdiri dari penelitian pendahuluan, fase pembuatan prototipe, dan fase penilaian. Subjek penelitian terdiri dari 39 siswa kelas lima MIN 1 Cilegon City yang dipilih menggunakan teknik purposive sampling. Instrumen ini dikembangkan berdasarkan kerangka teoritis NCTM dengan empat indikator komunikasi matematis pada materi KPK dan GCD. Instrumen yang dikembangkan memenuhi standar psikometri dengan validitas konstruksi yang sangat tinggi (koefisien korelasi r > 0,80 untuk semua item) dan keandalan tinggi (α = 0,861). Distribusi tingkat kesulitan menunjukkan satu item dalam kategori sedang (65,40%) dan tiga item dalam kategori sangat sulit (15,90%-17,80%). Kekuatan diskriminasi menunjukkan satu item dalam kategori yang memadai (0,341) sementara tiga lainnya membutuhkan perbaikan. Instrumen ini berhasil dikembangkan dengan kualitas psikometrik yang memadai dan dapat digunakan sebagai alat evaluasi kemampuan komunikasi matematika di Madrasah Ibtidaiyah. Penelitian di masa depan disarankan untuk memperluas sampel penelitian dan mengembangkan instrumen untuk materi matematika lainnya.